Relationship between occupational stress and turnover intention among employees in a plastic manufacturing company (Guppy Plastics Industries Sdn. Bhd.) / Siti Nur Salbiah Mat Anuwar and Nor Syazwanie Jamahari - Mat Anuwar, Siti Nur Salbiah; Jamahari, Nor Syazwanie (Faculty of Business and Management, 2016)
Turnover had been the greatest concern on the global company nowadays despite their competitiveness in retaining their best human capital to sustain their business. Turnover is defined as employees leave the organization intentionally where it should include plan and desire to quit. The occupational stress is the major factor that contributes to turnover intention due to employees that cannot cope with the stressor at work would experience intention to quit. Therefore, the purpose of this research is to investigate the relationship between role conflict, work overload and working environment toward turnover intention and to identify the most influential occupational stress factors toward turnover intention at Guppy Plastics Industries Sdn. Bhd. This research is a quantitative research which used the self-administered questionnaire as instruments to collect data. The data had been collected from 93% of 118 respondents which withdrawn from the total 167 element of population by using simple random sampling method. The data collected is then evaluated by using Statistical Package for the Social Science (SPSS) Version 20 Software. Thus, Pearson Correlation analysis indicates that there is positive significant relationship between role conflict and work overload toward turnover intention, however, there is no negative significant relationship between working environment and turnover intention. While, regression analysis revealed that the most influential occupational stress factor toward turnover intention is role conflict.